The ultimate power nap for rapid rest and renewal - Ginandes, Carol; Crown House Publishing (United States : Crown House Publishing Ltd, 2009)
This is an easy-to-use program which teaches the listener how to take brief, effortless but deeply restorative naps and also how to awaken on time feeling alert and replenished
Disc 1.- Introduction.- Practice session. Disc 2.- Prepare to nap.- The power nap
Title from container
CD-AUDIO format
Keywords: Naps (Sleep)